L’analyse de l’activité de démaillage : intérêts pour et dans la conception d’un filet de pêche biodégradable - Tabatha Thiébaut-Rizzoni; Laurent Guillet; Julie Lassalle; Christine Chauvin (Activités)
Fishing is a risky activity that has been mainly studied in ergonomics in order to optimize safety on board. The current ecological situation has led us to take an interest in a new way of fishing in order, among other things, to design more environmentally friendly fishing gear. Until now, no study has focused on how fishermen use fishing gear. Based on in situ observations on board two fishing boats and on explicitating self-confrontation interviews with four sailors, this study describes the use of fishing nets at different levels of the fishing activity: macro, meso and micro. It highlights the mechanical stress suffered by fishing nets and the patterns of use mobilized by the deckhands during the unmeshing of the catch. The results help to enrich the specifications for the design of biodegradable fishing gear, to enlighten the design teams on real fishing activity, and to build an environment facilitating the transition from current fishing practices to more sustainable ones.